PERANAN UNDANG-UNDANG PEMBERANTASAN KORUPSI TERHADAP SAKSI (KASUS RUMAH POTONG HEWAN PEMERINTAH KOTA BALIKPAPAN) - Gusti Heliana Safitri (LEGALITAS : Jurnal Ilmiah Ilmu Hukum, 2018)
The aim of this research is to know the corruption in Balikpapan City onthe building of the Rumah Potong Unggas (Chicken Cutting Place). Theresearch method is library one. The data and analysis are taken from thelocal daily news paper. The location of the research is in Balikpapanduring 6 (six) months in 2018/2019. The results of it are (1) Thecorruption strongly happened on the building of RPU Rumah PotongUnggas (Chicken Cutting Place) in Balikpapan; (2) The corruption actionis held by many people; (3) The people involved are from executive andlegislative as well as non-state officers or some member of societyincluding the corporations; (4) The corruption deed is concerning “markup”of the budget. The suggestions are : (1) This action crime has to besolved stricktly; (2) The money corrupted has to be repayed; (3) The lawenforcement has to be executed.